2022
DOI: 10.1177/17562848221092593
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hospitalization and HIV severity on gastrointestinal PCR panel evaluation of HIV-related acute diarrhea in New York City: a retrospective, cross-sectional study

Abstract: Introduction: Diarrhea is common in persons living with HIV (PLWH)/AIDS. With the increasing utilization of multiplex gastrointestinal PCR panel (GI panel) testing, we aimed to characterize the roles of CD4 count and hospitalization in GI panel assessments of PLWH with acute diarrhea. Methods: We performed a cross-sectional study of adult PLWH with acute diarrhea who underwent GI panel testing at two urban academic centers. Demographic, HIV disease, GI panel result, and hospitalization data were collected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…24 In a study of GI PCR testing in patients with HIV, Axelrad et al found that 25% of men who have sex with men patients had multiple gut pathogens regardless of their degree of immunosuppression. 11,25 Our study was not powered to look at specific categories of immunosuppression and it is likely that there was heterogeneity in the degree of immunosuppression within the diverse group of immunosuppressed patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a study of GI PCR testing in patients with HIV, Axelrad et al found that 25% of men who have sex with men patients had multiple gut pathogens regardless of their degree of immunosuppression. 11,25 Our study was not powered to look at specific categories of immunosuppression and it is likely that there was heterogeneity in the degree of immunosuppression within the diverse group of immunosuppressed patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with weakened immune systems, such as those with HIV/AIDS or undergoing cancer treatment or organ transplantation, the body's normal defense mechanisms against colonization by gut pathogens are compromised. [6][7][8][9][10][11] Similarly, patients with comorbidities that disrupt the gut microbiome, such as cancer, diabetes, heart failure, chronic kidney disease, or inflammatory bowel disease (IBD), are more prone to enteric infections. 9,[12][13][14][15][16][17][18] We further hypothesized that the presence of multiple pathogens would be associated with measurably-worse clinical outcomes even after adjusting for other factors-i.e., that these patients would have true co-infection which would lead to increased healthcare utilization compared to singly-infected patients.…”
Section: Introductionmentioning
confidence: 99%